Intentions towards the sustainability of young adults: a cross-cultural comparison - Loureiro, S. M. C.; Kaufmann, H.R. (World Review of Entrepreneurship, Management and Sustainable Development, 2014)
Education for sustainable development in higher education is becoming increasingly important for success of universities and other institutions where students will exercise their professions. The main goal of this study is to apply the theory of planned behaviour to analyse sustainability attitudes, behaviours and intentions among students in higher education institutions across five countries: USA, Portugal, Cyprus, Serbia, and South Korea. The results suggest that individualism, masculinity, and power distance moderate the effects of attitude and behaviour on sustainable intentions. Individuals in more individualistic and masculine societies tend to be more pro-active and assertive in their attitudes, decisions, and reactions towards sustainability. In universities located in societies that score high in power distance, professors and senior managers must be very clear when defining and practicing sustainability issues in courses, classes and on campus.